Efektivitas Layanan Bimbingan Kelompok Dengan Permainan Tradisional (Gobak Sodor) Untuk Meningkatkan Interaksi Sosial Peserta Didik Kelas Iv-A di SD Negeri 1 Kalampangan - Siti Aminah; Sonedi Sonedi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to: (1) Know the social interaction profile of IV-A students in SD Negeri 1 Kalampangan, (2) Know the effectiveness of group guidance with traditional games (gobak sodor) to improve social interaction of IV-A students in elementary school Negeri 1 Kalampangan. The study population was 21 IV-A students in SD Negeri 1 Kalampangan with 21 students and 15 students as the research sample. The method used is an experiment, with the Pre-Post Design experiment that is analysis involving two measurements on the same subject against a particular influence or treatment. Data collection techniques in this study used observation and scale. The results of this study indicate that: (1) The level of social interaction of IV-A class students in SD Negeri 1 The results based on the results of the Paired Sample T-Test showed that social interaction behaviour had an initial increase of 40.10 (2) after given treatment (treatment) to the number of improvements on average by 72.50 with an average amount of increases of 30, (3) Meaning